Brief teaching sessions change behaviour in A&E. (9th October 2018) - Grant, Alexander; Stuttard, Matthew; Mitchell, Thomas
Summary: Background: The Accident and Emergency Department (A&E) is a busy environment that requires time‐ and resource‐efficient teaching. Managing cervical spine (c‐spine) trauma is often an unfamiliar skill for new doctors starting work in A&E. This study investigated the efficacy of brief teaching interventions in changing clinician behaviour within A&E. The Accident and Emergency Department is a busy environment that requires time‐ and resource‐efficient teaching Methods: Data for 482 patients receiving c‐spine computed tomography (CT) imaging in two Gloucestershire A&Es before and after multimodal departmental teaching were compared. Time taken to CT, indication for CT scan and presence of bony injury were manually recorded from patient management software. Results: Following the provision of teaching, the proportion of CT scans performed within 1 hour did not significantly change, from 31% before teaching to 37.6% after teaching (p = 0.133); however, the mean number of c‐spine CT scans performed per week rose from 14.50 to 23.25 (p = 0.0001), and the mean number of CT scans performed per week within 1 hour rose from 4.50 to 8.75 (p ≤ 0.001). There was no reduction in the quality of these scans, with the proportion detecting bony injury remaining constant, and there was no increase in the proportion of scans not indicated by National Institute for Health and Care Excellence guidelines. Conclusions: This study demonstrates that brief, low‐resource teaching can be associated with a positive change in clinician behaviour. This intervention was straightforward to implement and is likely to be transferable to other guideline‐driven investigations. Limitations include the patient cohort being proportionately older than that found in major trauma centres, and a lack of data on patients in whom CT scans were indicated but not performed.